OCCURRENCE AND IMPACT ANALYSIS FOR TIME-RELATED RISKS IN MALAYSIA PUBLIC INFRASTRUCTURE PROJECTS - Sim Nee, Ting; Jarit, Beatrice; Yee Yong, Lee (Penerbit UMT, 2022)
The public works sector in Malaysia has generally executed construction projects that are highly complex, requiring multiple components and involving a large scale of resources and management. Many construction works are carried out in rural settings with challenges and constraints in terms of site access, transportation and material availability. Hence, the problem of timely delivery of projects persists. It is critical to identify and manage schedule-related risks rigorously to ensure a successful and timely project delivery which is a precursor for the nation’s sustainable development. This study, part of efforts to set up a Malaysia-based risk registry, involves the identification of key risks related to scheduling in Malaysia’s public works infrastructure projects and the analysis of their occurrences and impacts. A total of 111 of 123 projects from the Sarawak state’s Public Works Department are studied via the case study method. The selection of projects was based on whether a project’s completion date was extended due to the occurrences of delay events. The number of occurrences is calculated based on the number of times a delay event occurred in the 111 projects. The impact analysis is carried out based on the total delay over the overall project delay for a project. The findings show that the most frequently occurring risk in the 111 projects is “exceptionally inclement weather”, “whereas risks related to land blockage”, “obstructions by others and approval from other authorities” are risks that caused high severity in terms of delay in schedule. Information obtained from this research is part of key effort for risk data and knowledge retention and dissemination which can be used for further risk analysis for future construction projects.